Solve for m
m\neq 0
\left(\exists n_{1}\in \mathrm{Z}\text{ : }\left(x>\pi n_{1}+\frac{\pi }{2}\text{ and }x<\pi n_{1}+\frac{3\pi }{2}\right)\text{ and }o=0\right)\text{ or }\exists n_{2}\in \mathrm{Z}\text{ : }x=2\pi n_{2}+\pi \text{ or }x=0
Solve for o
\left\{\begin{matrix}o=0\text{, }&\nexists n_{1}\in \mathrm{Z}\text{ : }x=\pi n_{1}+\frac{\pi }{2}\text{ and }m\neq 0\\o\in \mathrm{R}\text{, }&\left(x=0\text{ and }m\neq 0\right)\text{ or }\left(\exists n_{2}\in \mathrm{Z}\text{ : }x=2\pi n_{2}+\pi \text{ and }m\neq 0\right)\end{matrix}\right.
Share
Copied to clipboard
\frac{\mathrm{d}}{\mathrm{d}x}(r)xm=\frac{4+4\cos(x)}{1+\cos(2x)}ox
Variable m cannot be equal to 0 since division by zero is not defined. Multiply both sides of the equation by m.
\frac{\mathrm{d}}{\mathrm{d}x}(r)xm=\frac{\left(4+4\cos(x)\right)o}{1+\cos(2x)}x
Express \frac{4+4\cos(x)}{1+\cos(2x)}o as a single fraction.
\frac{\mathrm{d}}{\mathrm{d}x}(r)xm=\frac{\left(4+4\cos(x)\right)ox}{1+\cos(2x)}
Express \frac{\left(4+4\cos(x)\right)o}{1+\cos(2x)}x as a single fraction.
\frac{\mathrm{d}}{\mathrm{d}x}(r)xm=\frac{\left(4o+4\cos(x)o\right)x}{1+\cos(2x)}
Use the distributive property to multiply 4+4\cos(x) by o.
\frac{\mathrm{d}}{\mathrm{d}x}(r)xm=\frac{4ox+4\cos(x)ox}{1+\cos(2x)}
Use the distributive property to multiply 4o+4\cos(x)o by x.
0=\frac{4ox\cos(x)+4ox}{\cos(2x)+1}
The equation is in standard form.
m\in
This is false for any m.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}